A comparative analysis on Islamic and Buddhist perspectives on lesbian, gay, bisexual, and transgender (LGBT) - Ahmad, Mohd Firdaus; Abdul Rahim, Adibah (Partridge Publication, 2018)
The issue of LGBT has been discussed by different experts and scholars from many perspectives and fields of study. However, these perspectives include only those which are considered scientific in nature while religion is always excluded from the discussion. This